2020
DOI: 10.3390/v12080871
|View full text |Cite
|
Sign up to set email alerts
|

The RNAi Pathway Is Important to Control Mayaro Virus Infection in Aedes aegypti but not for Wolbachia-Mediated Protection

Abstract: Mayaro virus (MAYV), a sylvatic arbovirus belonging to the Togaviridae family and Alphavirus genus, is responsible for an increasing number of outbreaks in several countries of Central and South America. Despite Haemagogus janthinomys being identified as the main vector of MAYV, laboratory studies have already demonstrated the competence of Aedes aegypti to transmit MAYV. It has also been demonstrated that the Wolbachia wMel strain is able to impair the replication and transmission of MAYV in Ae. aegypti. In A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Most likely, overexpression of siRNA pathway factors in the midgut tissue alone is not sufficient to completely suppress virus infection, and a few viral particles that will succeed in escaping this tissue are still able to cause systemic infection. Overexpression of multiple siRNA pathway factors, including AGO2 that has shown restriction of Mayaro virus [ 73 ], in multiple tissues could potentially result in a level of refractoriness that would have an epidemiologically significant impact on disease prevalence if WT mosquitoes would be replaced with transgenic. Furthermore, simultaneous transgenic expression of multiple orthogonal antiviral factors is likely to further potentiate virus blocking.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, overexpression of siRNA pathway factors in the midgut tissue alone is not sufficient to completely suppress virus infection, and a few viral particles that will succeed in escaping this tissue are still able to cause systemic infection. Overexpression of multiple siRNA pathway factors, including AGO2 that has shown restriction of Mayaro virus [ 73 ], in multiple tissues could potentially result in a level of refractoriness that would have an epidemiologically significant impact on disease prevalence if WT mosquitoes would be replaced with transgenic. Furthermore, simultaneous transgenic expression of multiple orthogonal antiviral factors is likely to further potentiate virus blocking.…”
Section: Discussionmentioning
confidence: 99%
“…2 ) cells, highlighting the antiviral role of the exo-siRNA pathway against ASALV. Similarly, silencing or knockout of Ago2 or Dcr2 induced an increase in infection by the tested arthropod-borne alphaviruses ( 15 , 17 , 19 , 38 , 39 ). Furthermore, similar results have been found for arboviruses belonging to other virus families or orders ( 8 ), except for Zika virus (ZIKV), where no antiviral activity was reported for Ago2 in silenced cells ( 9 , 19 ).…”
Section: Discussionmentioning
confidence: 94%
“…ASALV replication is increased in both Ago2 silenced (Figure 5B, Table S2) and Ago2 or Dcr2 knock-out cells (Figure 2); highlighting the antiviral role of the exo-siRNA pathway against ASALV. Similarly, silencing or knock-out of Ago2 or Dcr2 induced an increase in infection of tested arthropod-borne alphaviruses (Campbell et al, 2008; Schnettler et al, 2013; Sucupira et al, 2020; Varjak, Dietrich, et al, 2018; Varjak, Donald, et al, 2017). Furthermore, similar results have been found for arboviruses belonging to other virus families or orders (Liu et al, 2019), except for ZIKV, where no antiviral activity was reported for Ago2 (Scherer et al, 2021; Varjak, Donald, et al, 2017).…”
Section: Discussionmentioning
confidence: 98%